Enhancing Early Reading Skills in Young Children Through the Implementation of Alphabet Maze Game - Samad, Munawwarah; Fitriani, Dewi; Fariza, Siti Rahma; Shidqi, Dzulfikar Sauqy (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
Early reading ability is the initial ability of children in the form of the ability to recognize and voice letters. Based on the observations in TKN An-Nada Aceh Selatan, many children's early reading skills still do not recognize letters, have difficulty mentioning letters, are not able to recognize the sound of letters, are not able to mention letters, and are not able to recognize letter symbols. This study aims to determine the application of the letter maze to develop the early reading skills of children in TKN An-Nada Aceh Selatan. This type of research is an experiment with a one-group pretest-posttest design. The population in this study was 45 children, while the sample in this study was 15 children. Data collection techniques were done through observation and documentation. The pretest value obtained is 18.75, and the posttest value is 83.33. The value of tcount is 8.8, and the value of ttable is 1.745. This shows that the value of tcount> ttable is 8.8> 1.761, so there is a rejection of Ho and an acceptance of Ha. So, it can be concluded that there is a difference in the value between the tcount and the ttable, and it can be concluded that the application of the letter maze can develop the ability to read early childhood beginnings at TKN An-Nada Aceh Selatan.